Efficient Biocatalysis with Immobilized Enzymes or Encapsulated Whole Cell Microorganism by Using the SpinChem Reactor System. Issue 12 (11th October 2013) - Mallin, Hendrik; Muschiol, Jan; Byström, Emil; Bornscheuer, Uwe T.
<x xml:space="preserve">Abstract</x> The chambers of Trivial Pursuit: Locking immobilized enzymes or encapsulated whole cells into a compartment that is connected to the stirrer enables efficient reactions and facilitates the reuse of biocatalysts by using this SpinChem system. R‐ATA=(R)‐amine transaminase.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>